Pengembangan Kemampuan Seni Anak Melalui Kegiatan Meronce Menggunakan Manik-Manik Di TK Miftahul Anwar Negeri Agung Lampung Tengah - Ajeng Ninda Uminar (Departement of Mathematics Education, 2022)
Meronce is an activity that requires careful eye and hand coordination, through finger movements that insert threads into the ronce grains. Meronce is organizing by tying the components together with string. In meronce learning activities, children can develop artistic abilities, so that children don't just draw, sing, and color. Through children's activities they can develop artistic abilities with different activities. By using the demonstration method in meronce activities, learning activities become more effective so that it can become a training process for children. The focus of observation in this study was group B children, aged 5-6 years in Miftahul Anwar Kindergarten with 29 students (16 girls and 13 boys). In this study it can be concluded that through the beading activity in group B at Miftahul Anwar Negeri Agung Kindergarten the children were very enthusiastic about participating in learning, and it was effective for developing children's artistic abilities.